Education for arthritis patients: a community pharmacy based pilot project. - Petkova VB (Centro de Investigaciones y Publicaciones Farmaceuticas, 2009)
There are different kinds of arthritis, widely spread among the population, that make them a clinical problem with social, psychological and economic burden. Different education programs have been developed in order to improve patients' disease management, medication compliance and from there patients' quality of life.Objective: To develop and implement a community pharmacy-based educational program for patients with arthritis. Improvements in pain, medication compliance, decrease in general practitioner's visits and hospitalizations are expected.Methods: Prospective, randomized, controlled trial. The sample consisted of 43 individuals, with different stages of arthritis (aged 15 - 71), attending pharmacies - intervention group; and 43 individuals - control group. A 4-month education was conducted on the following topics: what causes arthritis and what are the factors that can intensify it; pain management and physical activities; self-management and prevention; pharmacotherapy and possible adverse drug reactions. Patient's health-related quality of life was assessed in the beginning and at the end of the survey. Results: Parameters assessed during the four stages of the program were: frequency of severe pain, frequency of general practitioner's visits, frequency of urgent medical aid calls, compliance with therapy, satisfaction with pharmacy services. Improvement in patients' health-related quality of life was observed and also: decrease in the severity of patients' pain, decrease in the physician's visits, and increase in satisfaction overall care.Conclusions: Positive results from the educational approach in pharmacy conditions were demonstrated. These consequences have a potential to increase arthritis patient's quality of life.